Eukaryotic elongation factor 2 kinase inhibitor, A484954 lowered blood pressure in spontaneously hypertensive rats via inducing vasorelaxation - Tomoko Kodama; Muneyoshi Okada; Hideyuki Yamawaki (Elsevier, 2020)
Eukaryotic elongation factor 2 (eEF2) kinase (eEF2K) suppresses protein translation. We previously reported eEF2K expression was upregulated in mesenteric arteries (MA) from spontaneously hypertensive rats (SHR). We have recently revealed A484954, an eEF2K inhibitor, acutely suppressed vasopressor agonists-induced increase of blood pressure (BP) in normal Wistar rats. In this study, we examined the acute effects of A484954 on BP in SHR and explored underlying mechanisms. BP was measured by a carotid cannulation method in SHR. Isometric contraction in MA from SHR was measured. Endothelial nitric oxide synthase (eNOS) dimerization was measured by low-temperature sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blotting. A484954 lowered BP in 15-week-old SHR. A484954 induced relaxation in MA from both 4- and 7-9-week-old SHR. In MA from 4-week-old SHR, A484954-induced relaxation was inhibited almost completely by a NOS inhibitor, NG-nitro-l-arginine methyl ester (l-NAME) and significantly by a β blocker, propranolol. In MA from 7-9-week-old SHR, on the other hand, A484954-induced relaxation was inhibited partly either by l-NAME, indomethacin, a cyclooxygenase inhibitor, or l-NAME + indomethacin. A484954 promoted the dimerization of eNOS in human endothelial cells. In summary, we have revealed A484954 lowers BP in SHR perhaps through the vasorelaxation via the production of endothelium-derived relaxing factors.